Analisis Keterlambatan Pembangunan Gedung Kampus Poltekkes Banten - Raharjo, Muji; Azhar, Moh. (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
In order to achieve maximum development, supervisory work is needed. Facilities and infrastructure are very vital and very important things in supporting the smoothness or convenience of the learning process, in relation to education that requires facilities and infrastructure and also their utilization both in terms of intensity and creativity in their use by lecturers and students in learning activities teach. Educational facilities are all the facilities needed in the teaching and learning process, both movable and immovable so that the achievement of educational goals can run smoothly, regularly, effectively and efficiently. In the 2021 fiscal year the Banten Poltekes campus received a budget of 9,779,346,000. The allocation of these funds was intended to continue the construction of the Phase VII Poltekes building, there were delays caused by disputes. These disputes stem from several factors between stakeholders, in which each stakeholder has different problems and this requires quite a long time to identify the causative factors and find the right solution. The purpose of this study was to analyze the factors causing delays in the construction of the Polytechnic Health Campus building in Banten. The research was conducted using a qualitative method by means of a narrative description, in which the researcher conducted interviews with the Director of PT. Rahandika Nusa Perkasa. The results of the study found that the factors causing the delay in the construction of the Poltekkes campus building in Banten were due to the very short time given, the selection of workers who were not good, the frequent exchange of workers, the lack of material transportation equipment.